Wujud Memayu Hayuning Bawana dalam Legenda Sendang Bulus Ponorogo - Pramudiyanto, Ahmad; Sari, Fitriana Kartika (DIWANGKARA: Jurnal Pendidikan, Bahasa, Sastra dan Budaya Jawa, 2024)
This article aims to describe the form of the Javanese philosophy of memayu hayuning Bawana in the Sendang Bulus Legend. Data was taken from the text of the Ponorogo Folklore Collection which was read heuristically and hermeneutically. The results of the study show that the form of the Javanese philosophy of memayu hayuning Bawana in the Sendang Bulus Legend shows an effort to achieve cosmos harmony as an effort to achieve holistic peace and tranquility. The manifestation of Javanese philosophy is found in the four directions of the nature of relationships, namely (1) the relationship between humans and God which is manifested in the behavior of prayer and surrender; (2) the relationship between humans and themselves in the form of ascetic activities which require humans to control their desires and concentrate their focus. to God; (3) the relationship between humans and each other which includes behavior to create mutual peace and tranquility; and (3) the relationship between humans and nature which is realized in the form of preserving ecosystems and the biological and non-biological diversity within them.